PENGARUH LAMA PENYIMPANAN TERHADAP FERTILITAS, SUSUT TETAS, DAYA TETAS DAN BOBOT TETAS TELUR AYAM ARAB - Irma Susanti; Tintin Kurtini; Dian Septinova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The Arabic chicken is superior layer chicken, that has high ability to produce egg, i.e 230—250 eggs/chicken/year. Generally, the Arabic chicken was use as layer chicken and not to use as broiler chicken. One the effecting factor to fertility, hatching desrease, hatching strength and hatching weight is storage duration. The purpose of this research are (1) to assest the effect storage duration of the Arabic chicken egg to fertility, weight loss, hatching eggs, and hatching weight and (2) to determine the best storage duration to fertility, weight loss, hatching eggs, and hatching weight. This research was done on December 13th, 2014 until January 8th, 2015 at Ilham hatchery, Tegal Rejo village, Gadingrejo subdistrict, Pringsewu regency. This research use the complete randomize design with 3 treatments and 6 times replication. Every treatment use 9 of the Arabic chicken eggs. The weight eggs average is 41,18 ± 2,18 gram/egg with ± 5, 31% uniformity coeffisien. If the treatment given the significant effect to definite variable (P<0,05), the analyzed will be continue with Duncan test. The research result shown that storage duration have significant effect (P<0,05) to hatching eggs , but have not significant effect (P>0,05) to fertility, weight loss, and hatching weight of the Arabic chicken egg. Keywords : Egg storage duration, fertility, weigh loss, hatching eggs, hatching weight, and Arabic chicken